Fruit Quality Analysis of Kiwifruit Cultivars Cultivated in Eastern Mid-Hills in Nepal - Poudel, K .; Shah, M. K.; Mandal, J. L. (Journal of Agriculture and Environment, 2019)
Available with full text.